Medium‐term evolution in French national newspaper coverage of the interrelations between biodiversity and agriculture - Julie Delclaux; Philippe Fleury (Conservation Science and Practice, 2021)
Abstract Agricultural landscapes are sites of difficult trade‐offs between conservation and production objectives. The media play a part in shaping public opinion and policies and vice‐versa. In line with the constructionist approach to public problems, we analyzed the role of media in the problem‐framing of interrelations between biodiversity and agriculture. We investigated the medium‐term evolution in French national newspaper coverage of these interrelations using a content and time analysis over a 19‐year period (1999–2017). We applied a statistical method using IRaMuTeQ (interface of R) on seven daily newspapers (Le Monde, Libération, La Croix, Les Échos, Le Figaro, L'Humanité, and La Tribune; N = 2,547). Our results reveal the growing importance of agriculture in the public problem of biodiversity loss. The increase of agriculture/biodiversity coverage is driven by environmental issues and specific political events. However, the number of articles focused on biodiversity/agriculture dynamics remains low. Around 2007, the articles shifted from an international species‐centered view to a national and local human‐centered view. These evolutions in media‐coverage create a space for ecologists, social scientists, and agronomists to combine their approaches and to develop and communicate on new actions in favor of biodiversity in agricultural landscapes.